Local Newspapers in Japan: News and Memory Creation. (June 2016) - Seward, Robert
Anthony Rausch, ed. Japanese Journalism and the Japanese Newspaper—A Supplemental Reader. Amherst, New York: Tenneo Press, 2014. 281 pp. Includes bibliographical references and index. ISBN 978-1-934884-70-0 paper